(untitled) (Biological Sciences - PJSIR, 2000)
The complex formation process of 1,3-diphenylpyrazole -4-carboxaldehyde -2-chlorobenzoyl-hydrazore with differ- ent transition and non transition metals were investigated and complexes have been characterized through their metal analysis and by applying spectrophotometric techniques. Job’s continuous variation method has been used to calculate the stability constant and stoichiometry of the complexes. The mode of complexation has been studied with the help of infra-red technique. A proposed structure of the complexes involving co-ordination through nitrogen and oxygen of the hydrazone moiety with different metals has been represented.